KEPEMIMPINAN TRANSFORMATIF PENDIRI YAYASAN DALAM MENINGKATKAN KINERJA PENGASUH PONDOK PESANTREN BUSTANUT THOLIBIN SEMANDING TUBAN - Moh Agus Sifa'; A Halil Thahir; M Thoyyib (Prodi Manajemen Pendidikan Islam Universitas Al-Hikmah Indonesia, 2025)
This study aims to analyze the role of transformational leadership of the founder of the Karang Bumi Santri Foundation in improving the performance of the caretakers of the Bustanut Tholibin Semanding Tuban Islamic Boarding School. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed inductively. The results of the study indicate that the transformational leadership model applied by the founder of the foundation, especially H. Subagio, focuses on vision, inspiration, exemplary behavior, and individual attention to the caretakers. Uniquely, the caretakers do not come from dzurriyah kyai, but are appointed based on competence by the foundation, so that the relationship between the foundation and the caretakers is functional and contractual. During the 2021–2025 period, there were three changes of caretakers as a form of continuous evaluation. The caretaker's performance was assessed not only from scientific competence, but also from managerial abilities, discipline, communication, and the suitability of the vision with the foundation. This finding confirms that transformational leadership plays an important role in creating stability, sustainability, and progress of Islamic boarding schools.